FIRST REPORT OF RINAMBA PLATYFEMUR (MARSH) (HYMENOPTERA: BRACONIDAE) IN MEXICO - Cauich-Kumul, Roger; Delfín-González, Hugo; López-Martínez, Víctor (Instituto de Ecología, A.C., 2013)
The braconid wasp Rinamba platyfemur (Marsh) (Hymenoptera: Braconidae) is reported for first time for Mexico;Yucatan Peninsula its northernmost distribution record.